Subject classification of literary artistic images - Shamyakina, Slavyana V. (Journal of the Belarusian State University. Philology, 2022)
The purpose of the work is to create an integral classification of the types of literary artistic images, distinguished on the basis of a special subject of the image. Throughout the history of literary criticism, researchers have substantiated the presence in literary works of various types of artistic images that have a specific subject of image, but so far there has not been a single classification that systematises scientific ideas about all such types of images. In this work, the author summarises this information and groups the variety of images into several types based on the proximity of the objects of the image. So, the following types of artistic images in literary works are distinguished: animate images, image of space, object images and polysubject images. Animate images represent various ways and forms of description in literary works of man and other living beings (animals, plants, mythological and fantastic creatures). Images of space are structural elements of the artistic space of a literary work. Object images are semantically related to certain inanimate material objects (things) or groups of objects. Polysubject images have several different objects of the image, they are semantic structures of a more complex level, including other types of images with specific objects of the image. Animate images include an image-personage, a lyrical hero, images of the author and reader, animals and herb, the image of the nation. Among the images of space are paysage, locus and topos. Object images are subdivided into such types as image-thing, interior and exterior. The type of polysubject images includes the image of a country, a chronotope, an image of the world and a picture of the world. The work gives definitions for each variety and type of images and presents the author’s concepts on the criteria for their differentiation.